1996
DOI: 10.1016/s0377-0257(96)01476-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-Newtonian shear-thinning flows past a flat plate

Abstract: The present work attempts to characterize the flow of shear-thinning power-law fluids past a flat plate as the angle of attack is varied. The effects of Reynolds number, shear-thinning characteristics and angles of attack on drag and lift of the flat plate were investigated, both experimentally and numerically. Carbopol 940 solutions of various strengths were used to approximate purely viscous shear-thinning non-Newtonian fluids for the experiments. An important finding is that at small angles of attack when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 10 publications
(16 reference statements)
3
24
0
Order By: Relevance
“…However, for the normal configuration, the flow is unlikely to be steady as has been assumed in this study. Also, while his values of the critical Reynolds number in shear-thinning fluids are consistent with that of Wu and Thomson [26], the corresponding values in shear-thickening (n > 1) fluids are very high indeed, e.g., Re $ 10 6 for n = 2. In other words, the boundary layer flow approximation provides a very poor representation for shear-thickening fluids.…”
Section: Previous Worksupporting
confidence: 79%
See 1 more Smart Citation
“…However, for the normal configuration, the flow is unlikely to be steady as has been assumed in this study. Also, while his values of the critical Reynolds number in shear-thinning fluids are consistent with that of Wu and Thomson [26], the corresponding values in shear-thickening (n > 1) fluids are very high indeed, e.g., Re $ 10 6 for n = 2. In other words, the boundary layer flow approximation provides a very poor representation for shear-thickening fluids.…”
Section: Previous Worksupporting
confidence: 79%
“…In contrast, despite the frequent occurrence of shear-thinning and yield stress fluids in scores of industrial settings, little numerical and experimental studies on the momentum and heat transfer characteristics for this configuration in such fluids have been reported in the literature. For instance, in an extensive study, Wu and Thompson [26] studied the effect of angle of incidence of power-law (n < 1) fluids on a two-dimensional plane surface. Their experimental results of drag coefficients for both tangential and transverse flow were consistent with their finite element method based predictions up to about Re $ 10.…”
Section: Previous Workmentioning
confidence: 99%
“…A similarity solution to the boundary-layer flow of a power-law non-Newtonian fluid over a horizontal flat plate was obtained in [11]. Wu and Thompson [12] experimentally found that even if the Reynolds number is not large, the boundary-layer equations are still valid and accurate for the flow of shear-thinning fluids. Denier and Dabrowski [13] investigated the boundary-layer equations describing the steady uniform flow of a non-Newtonian fluid past a flat plate.…”
Section: Introductionmentioning
confidence: 99%
“…Single constitutive equation exhibiting all the properties of non-Newtonian fluids is not available due to the diversity of these fluids in their constitutive behavior, simultaneous viscous and elastic properties. Thus, several models of non-Newtonian fluids have been proposed to fit well with the experimental observations [5]. The non-Newtonian fluids can be classified into the following three types, i.e., (i) differential type (ii) rate type and (iii) integral type.…”
Section: Introductionmentioning
confidence: 99%